Tensile Strength Comparison of Polymer Composite Materials Reinforced by Three Types of Bamboo Fiber Treated With 5% aq. NaOH Solution - Ahmad Nayan; Muhammad Yusuf; Deassy Siska (Malikussaleh University, Aceh, Indonesia, 2023)
The specimens were prepared with polyester polymer reinforced with natural fiber from three types of bamboo, namely Gigantochloa Apus, Bambusa vulgaris, and Bambusa blumeana. Their tensile properties were compared and investigated. In this paper, the specimen utilization of hand-wet layup processes of polyester resin with natural fibers. The fibers were treated with 5% NaOH solution to remove hemicellulose and create better debonding between matrix and fiber. Bamboo-reinforced composite of 3 types of bamboo with fractions 60% volume is thorn bamboo, Bambusa vulgaris, Gigantochloa Apus, and bamboo wipe without alkali. Of the three types of bamboo, the highest tensile strength of Gigantochloa Apus was soaked using NaOH with an average value of 37.06 MPa, with a tensile strain of 4.11%. In contrast, the lowest tensile strength value is Gigantochloa Apus which was not immersed in NaOH with an average of 13.79 MPa, a tensile strain of 2.54%. This matter shows the effect of immersion on tensile strength bamboo fiber composite. The results of the tensile strength of each type of bamboo obtained in this research, among others, bamboo thorn's tensile strength of 22.81 MPa, Bambusa vulgaris tensile strength of 16.69 MPa, bamboo apus 37.06 MPa, and Gigantochloa Apus without alkali 13.79 MPa. The observations show that Gigantochloa Apuscomposites are suitable for use as alternative tensile materials.